2011
DOI: 10.1016/j.taap.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel indicators of cyclosporine A nephrotoxicity in a CD-1 mouse model

Abstract: Publication informationToxicology and Applied Pharmacology, 252 (2): 201-210 Publisher ElsevierLink to online version http://dx.doi.org/10.1016/j.taap.2011.02.015Item record/more information http://hdl.handle.net/10197/2887Publisher's statement All rights reserved. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Markers of structural damage, such as neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule 1 (KIM-1) (95,96 ), respond early but may also signal other sources of kidney injury. Research efforts to discover new biomarkers that reveal very early CnI nephrotoxicity more specifically have pointed to several candidates in close proximity to the disturbed Cn-signaling pathway, such as TGF-␤ and its downstream modulators CTGF (connective tissue growth factor) and BMP-7 (bone morphogenetic protein 7), known mediators of tubulointerstitial fibrosis (97 ). Alternatively, toxicogenomic studies have identified molecular mechanisms that may specifically reveal CsA toxicity, such as endoplasmic reticulum stress and the epithelial-to-mesenchymal transition.…”
Section: Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…Markers of structural damage, such as neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule 1 (KIM-1) (95,96 ), respond early but may also signal other sources of kidney injury. Research efforts to discover new biomarkers that reveal very early CnI nephrotoxicity more specifically have pointed to several candidates in close proximity to the disturbed Cn-signaling pathway, such as TGF-␤ and its downstream modulators CTGF (connective tissue growth factor) and BMP-7 (bone morphogenetic protein 7), known mediators of tubulointerstitial fibrosis (97 ). Alternatively, toxicogenomic studies have identified molecular mechanisms that may specifically reveal CsA toxicity, such as endoplasmic reticulum stress and the epithelial-to-mesenchymal transition.…”
Section: Kidneymentioning
confidence: 99%
“…Diagnostic markers of these processes, such as the chaperone protein BiP and the epithelial marker E-cadherin, are currently being evaluated as potential biomarkers of early kidney damage in CsAtreated renal allograft recipients (98 ). Urine screening in mice receiving CsA revealed several proteins that may also qualify as biomarkers of early kidney damage, including vinculin, podocin, uromodulin, and, again, E-cadherin (97 ).…”
Section: Kidneymentioning
confidence: 99%
“…Early diagnosis of nephropathy can greatly improve patient diagnosis, but the initial stages of CsA-induced nephropathy are largely asymptomatic, making early diagnosis difficult [13]. Since the current diagnostic techniques employed to detect CsA nephropathy seem to be unsatisfactory, the identification of novel, early disease indicators is currently a major research focus.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable advantage of using a quantitative MS-based proteomic approach as opposed to transcriptomic screening is that it allows detecting cellular responses directly at the protein level. Several reports on protein expression in CsA-exposed cells were recently published, most of which however employed 2-DE image analysis, resulting in a relatively small number of proteins identified and quantitated, due to the low throughput and lack of reproducibility of coupling 2-DE for protein quantification with MS for protein identification [16,28]. Recently, we successfully applied SILAC to study altered expression level of intracellular proteins in HEK-293 cells exposed to 5 μM CsA [20].…”
Section: Discussionmentioning
confidence: 99%